2017
DOI: 10.1094/pdis-07-16-0975-re
|View full text |Cite
|
Sign up to set email alerts
|

Time Interval Between Cover Crop Termination and Planting Influences Corn Seedling Disease, Plant Growth, and Yield

Abstract: Experiments were established in a controlled-growth chamber and in the field to evaluate the effect of the length of time intervals between winter rye cover crop termination and corn planting on corn seedling disease, corn growth, and grain yield in 2014 and 2015. Rye termination dates ranged from 25 days before planting (DBP) to 2 days after planting (DAP) corn in the field and from 21 DBP to 1 DAP in controlled studies. Results were similar in both environments. In general, shorter intervals increased seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
5
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(128 citation statements)
references
References 55 publications
9
96
5
4
Order By: Relevance
“…Increased risk of pest and diseases following a cover crop can also result in corn yield decrease. A rye cover crop can act as a host to root rot and seedling disease pathogens which may result in the infection of corn seedlings (Acharya et al, 2017; Bakker et al, 2016). The chance of disease and pest infection can be lessened by increasing the interval between rye termination and corn planting.…”
Section: Resultsmentioning
confidence: 99%
“…Increased risk of pest and diseases following a cover crop can also result in corn yield decrease. A rye cover crop can act as a host to root rot and seedling disease pathogens which may result in the infection of corn seedlings (Acharya et al, 2017; Bakker et al, 2016). The chance of disease and pest infection can be lessened by increasing the interval between rye termination and corn planting.…”
Section: Resultsmentioning
confidence: 99%
“…In past studies, cover crops such as cereal rye have been implicated at increasing corn pathogen densities leading to reduced disease suppressive soil function (Acharya et al. , Bakker et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bakker et al (2016) demonstrated that the dying roots of winter cereal rye cover crops harbour high populations of corn seedling pathogens. Moreover, Acharya et al (2017) showed that corn following a winter cereal rye cover crop had greater seedling disease incidence than corn following a winter fallow, and that lower corn yields in one year of the study were partly explained by reduced stands and poor plant vigour caused by soil-borne pathogens. In their study, increased levels of members of Pythium Clade B were recovered from corn seedlings grown after winter cereal rye while no effect of winter cereal rye on Fusarium species was detected (Acharya et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Winter cereal rye (Secale cereale L.) is the most commonly used cover crop species in Iowa because it survives the Midwest winter and produces a substantial amount of biomass before planting of the next cash crop in spring (Snapp et al, 2005). However, occasionally a winter cereal rye cover crop may negatively affect corn yield (Kaspar & Bakker, 2015;Acharya et al, 2017) and consequently many farmers are reluctant to incorporate cover crops into their production systems. This occasional yield loss of corn following a winter cereal rye cover crop has been attributed to several biotic and abiotic factors, including reduced inorganic nitrogen and water availability due to cover crop uptake, inhibitory allelochemicals from living or dying winter cereal rye plants, immobilization of nitrogen during decomposition of the cover crop, poor plant performance associated with dense plant residue and near-surface roots, and increased pest pressure (Mitchell & Tell, 1977;Ebelhar et al, 1984;Wagger & Mengel, 1988;Karlen & Doran, 1991;Tollenaar et al, 1993;Kessavalou & Walters, 1997;Duiker & Curran, 2005).…”
Section: Introductionmentioning
confidence: 99%